The Israeli Digital Rights Movement's campaign for privacy - Efrat Daskal (Internet Policy Review, 2017)
This study explores the persuasion techniques used by the Israeli Digital Rights Movement in its campaign against Israel's biometric database. The research was based on analysing the movement's official publications and announcements and the journalistic discourse that surrounded their campaign within the political, judicial, and public arenas in 2009-2017. The results demonstrate how the organisation navigated three persuasion frames to achieve its goals: the unnecessity of a biometric database in democracy; the database's ineffectiveness; and governmental incompetence in securing it. I conclude by discussing how analysing civil society privacy campaigns can shed light over different regimes of privacy governance.
Keywords: 300; Privacy; Government surveillance; Biometric